Webinar Pengabdian Kepada Masyarakat Implementasi Indikator Kinerja Dalam Dunia Bisnis - Ahmad Azmy (Universitas Mathla'ul Anwar Banten, 2022)
COMMUNITY SERVICE WEBINAR IMPLEMENTATION OF PERFORMANCE INDICATORS IN THE BUSINESS WORLD. This webinar is held to share knowledge and practice about the application of performance management in the business world. The theme taken is more specific about the implementation of performance indicators. The webinar planning process was prepared by a committee team from the Management Study Program, Faculty of Economics and Business, Paramadina University. The webinar method is carried out virtually using the Google Meet platform. The resource persons come from lecturers and practitioners with a balance between conceptual and practical application of performance indicators in the company. The number of participants for the webinar was 51 people. Webinar evaluation conducted by webinar participants assessed that the material presented could be understood well. The ability of the committee, resource persons, and moderators was considered good during the webinar. Participants are satisfied with the implementation of the webinar and hope there will be a continuation of the event.